2009
DOI: 10.1063/1.3054383
|View full text |Cite
|
Sign up to set email alerts
|

Phonon scattering at a rough interface between two fcc lattices

Abstract: Elastic phonon scattering at an atomically rough interface that separates two fcc lattice leads is computed via a Green's function method. Results are compared to specular and diffuse phonon scattering models, both of which are widely used in the numerical simulations of phonon Boltzmann transport equations. The shape of the discrete interface in the model is quantified by its spectral characteristics. It is found that the amplitude of the interface height fluctuations has strong influence on the effective int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 16 publications
(19 reference statements)
9
57
0
Order By: Relevance
“…For single Si/Ge interfaces, effects of strain [23], lattice mismatch [24], and interface roughness [25,26] on phonon transmission have been investigated. Green's function study on Si/Ge superlattices, however, is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…For single Si/Ge interfaces, effects of strain [23], lattice mismatch [24], and interface roughness [25,26] on phonon transmission have been investigated. Green's function study on Si/Ge superlattices, however, is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they studied the dependence of junction thermal conductance on junction length using both SBM calculations and NEMD simulations. 33 Tian et al 34 studied Si-Ge superlattice junctions using a harmonic lattice-based technique, 35,36 where they found that the introduction of disorder at interfaces destroyed coherent transport of phonons, particularly those with high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the frequency-dependent phonon transmission across a variety of material interfaces has been studied using the AGF approach, such as the interface in low dimensional atomic chains, 26 strained Si/Ge interface, 27 metal/graphene nanoribbon (GNR) interface, 28 rough interface between two face-centered cubic (FCC) crystals, 29 and more recently across confined material interfaces. 30 However, all the past AGF-based studies on phonon transmission across interfaces [27][28][29][30][31][32] focused on lattice-matched material interfaces, where the inter-atomic distance of one material is usually adjusted to match that in the other material in the directions parallel to the interface to simplify the calculations. For example, Si (or Ge) is strained to have the same lattice constant as Ge (or Si) along the interface plane to study phonon transmission across Si/Ge interface while the inter-atomic distance in the direction perpendicular to the interface is adjusted according to the Poisson's ratio in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 29, two FCC crystals with mass ratio and force constant ratio inherited from Si and Ge are used for the study of phonon transmission across rough interfaces and the lattice constants of the two crystals are adjusted to match each other. In the latticematched systems, perfect atomic bonds similar to the ones in their constituent materials are formed at the interface, with no bond breaking or reconstruction, since the inter-atomic distance is the same for both materials at the interface.…”
Section: Introductionmentioning
confidence: 99%